A Detour for Yeast Oxysterol Binding Proteins - Beh, Christopher T. (American Society for Biochemistry and Molecular Biology, 2012)
Oxysterol binding protein-related proteins, including the yeast proteins encoded by the OSH gene family (OSH1–OSH7), are implicated in the non-vesicular transfer of sterols between intracellular membranes and the plasma membrane. In light of recent studies, we revisited the proposal that Osh proteins are sterol transfer proteins and present new models consistent with known Osh protein functions. These models focus on the role of Osh proteins as sterol-dependent regulators of phosphoinositide and sphingolipid pathways. In contrast to their posited role as non-vesicular sterol transfer proteins, we propose that Osh proteins coordinate lipid signaling and membrane reorganization with the assembly of tethering complexes to promote molecular exchanges at membrane contact sites.